2017
DOI: 10.3390/ijms18071571
|View full text |Cite
|
Sign up to set email alerts
|

The Prostaglandin EP3 Receptor Is an Independent Negative Prognostic Factor for Cervical Cancer Patients

Abstract: We know that one of the main risk factors for cervical cancer is an infection with high-risk human papillomavirus (HR-HPV). Prostaglandins and their receptors are very important for the tumour growth and tumour-associated angiogenesis. Little is known about the expression of the Prostaglandin E receptor type 3 (EP3) or the Prostaglandin (PG)E2-EP3 signalling in cervical cancer, so the aim of the study was to analyse the expression of the EP3 receptor in cervical cancer and find prognostic factors in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
(34 reference statements)
0
26
1
Order By: Relevance
“…Another study observed that upregulation of EP3 expression in prostate cancer cells is associated with preventive and anticancer effects 45 . We observed that the prostaglandin EP3 receptor was an independent negative prognostic factor for cervical cancer 11 . www.nature.com/scientificreports www.nature.com/scientificreports/ Previous studies found a correlation between galectin-3 and the development of cervical cancer.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Another study observed that upregulation of EP3 expression in prostate cancer cells is associated with preventive and anticancer effects 45 . We observed that the prostaglandin EP3 receptor was an independent negative prognostic factor for cervical cancer 11 . www.nature.com/scientificreports www.nature.com/scientificreports/ Previous studies found a correlation between galectin-3 and the development of cervical cancer.…”
Section: Discussionmentioning
confidence: 69%
“…For this combined analysis we used the whole number of patients enrolled in our study (n = 250), no pre-selection was done. Our previous study demonstrated that high EP3 expression was associated with a poor overall survival rate of the same patients 11 . In the subgroup of cervical cancer patients with no EP3 expression www.nature.com/scientificreports www.nature.com/scientificreports/ (IRS score = 0, n = 45/250, 18%), the survival rate differed in the high-EP2 (n = 29/45, 64%) ( Fig.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Substrate-staining was performed for two and a half minutes with DAB (chromogen substrate kit, Dako, Hamburg, Germany). Counterstain by hemalaun colouring and dehydrogenation in an ascending alcohol series followed, before the slides were mounted with "Eukitt" (Orsatec, Bobingen, Germany) (Heidegger et al 2017). According to information in the human protein atlas sigma and placenta tissue were chosen as positive control.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Heidegger et al previously indicated that the prostaglandin E2-receptor EP3 is an independent negative prognostic factor in cervical cancer patients. The expression levels and the clinical outcome were proven to correlate with tumour stage (Heidegger et al 2017). In addition, Hester et al demonstrated that EP3 receptor expression levels correlate inversely with grades of CIN (Hester et al 2019).…”
Section: Introductionmentioning
confidence: 99%